The Role of Office Administration in Optimizing Public Services at the Ujung Pandang District Office - Nur Rezky Amalia; Haedar Akib; Herlina Sakawati (ASHA Publishing, 2024)
Providing services to the community is a form of government function in realizing. This research aims to determine the mechanism for implementing the role of office administration in optimizing public services at the Ujung Pandang Subdistrict Office and the factors inhibiting office administration in optimizing the Ujung Pandang Subdistrict Office. This type of research uses a qualitative approach where the research carried out is descriptive, namely, to describe the reality of events that occurred in the field during the research, which makes it easier for this research to obtain objective data in order to determine the role of office administration in optimizing public services at the Ujung Pandang Subdistrict office. Research data was collected using interviews and observations and then analyzed using descriptive statistics by collecting, compiling, reducing and verifying data. This research shows that the implementation of office administration services at the Ujung Pandang sub-district office is quite optimal, as can be seen from the fast and simple administrative procedures as a requirement for providing services as well as comprehensive information related to the administration mechanism for every form of management by the community. The forms of service available at the Ujung Pandang sub-district office include administrative services, goods services, services and regulatory services. Factors inhibiting the role of administration in public services at the Ujung Pandang District Head's office are the lack of facilities to support the continuity of administration, human resources that need to be strengthened again by providing understanding or training related to secretariat to each related staff.